Assessment on detection of biofilm in Escherichia coli, Erwinia carotovora, Bacillus subtilis and Xanthomonas oryzae pv. oryzae - Mohd Rifaie, Muhammad Aisamuddin (2017)
Biofilm is a colony of microorganism that attached to a particular surface and covered by the extracellular polymeric substance (EPS). Biofilm can be produced by microorganism such as bacteria, algae and fungi. Most bacteria reproduced in the free state but generally the bacteria attached to a surface and form colonies started from a single cell and developed into multilayers and live in colonies that more complex. The objectives of this study were to identify type of bacteria which can produce biofilm and evaluating the best method for detection biofilm formation. The methods used in this presentstudy are microtiter plate (MC), tube method (TM) and congo red agar method (CRA). In total, four type of isolates bacteria such as Escherichia coli, Bacillus subtilis, Erwinia carotovora and Xanthomonas oryzae pv.oryzae were subjected to biofilm detection. The microtiter plate method was considered to be the best method compared to TM and CRA. The microtiter plate method was found more consistent in producing results in this experiment, more quantitative and reliable method in detection of biofilm forming microorganisms compared to TM and CRA. In contrast, TM and CRA methods were less consistent and sensitive in detecting biofilm forming microorganisms.